2018
DOI: 10.1002/jso.25168
|View full text |Cite
|
Sign up to set email alerts
|

Surgical oncology at a major referral center in Ghana: Burden, staging, and outcomes

Abstract: Improved capacity for both therapeutic and palliative cancer care is needed to achieve better outcomes by more appropriate allocation of surgery with respect to the goal of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…However, a majority of operated patients underwent surgery with curative intent. This result is in agreement with reports from Ghana where surgery was done in curative intend in 60% of patients [21], but different from reports from Malawi where the vast majority of surgical procedures were of palliative intent [14].…”
Section: Treatment Details and Outcomessupporting
confidence: 81%
See 1 more Smart Citation
“…However, a majority of operated patients underwent surgery with curative intent. This result is in agreement with reports from Ghana where surgery was done in curative intend in 60% of patients [21], but different from reports from Malawi where the vast majority of surgical procedures were of palliative intent [14].…”
Section: Treatment Details and Outcomessupporting
confidence: 81%
“…CT and MRI are available in our country, therefore adequate staging was available for 92% of patients who had confirmed diagnosis of cancer. This rate is better than that report from Ghana [21], Malawi [14] and Pakistan [22].…”
Section: Treatment Details and Outcomescontrasting
confidence: 70%
“…From the single-country studies, majority were done in Nigeria ( n = 17) ( 24 , 25 , 28 , 29 , 34 , 45 , 54 , 64 , 72 , 75 , 92 , 93 , 103 , 113 , 116 , 124 , 137 ) and South Africa ( n = 20) ( 10 , 26 , 36 , 42 , 55 , 65 , 80 83 , 86 , 88 , 89 , 91 , 98 , 105 , 110 , 125 , 129 , 135 ), followed by Uganda ( n = 10) ( 35 , 40 , 48 , 59 , 74 , 78 , 79 , 90 , 94 , 95 ), then Malawi ( n = 9) ( 37 , 52 , 53 , 56 , 66 68 , 118 , 133 ) and Ethiopia ( n = 9) ( 33 , 51 , 63 , 97 , 101 , 107 , 112 , 146 , 157 ). We also found studies conducted in Ghana ( n = 6) ( 50 , 71 , 111 ,…”
Section: Resultssupporting
confidence: 53%
“…Two studies were from South Africa, one retrospective record review ( 26 ) and a cross-sectional study of Demographic and Health Survey (DHS) data ( 125 ). Two studies were from Ghana, of which one was a cross-sectional study ( 134 ) and the other a retrospective record review of patient files ( 50 ). There was one study from each of the following countries: a retrospective record review of pathology reports from the Central African Republic ( 32 ), another retrospective record review of non-governmental records in Botswana ( 43 ), one cross-sectional study from Sudan ( 114 ), one cross-sectional study in both South Africa and Uganda ( 120 ), one retrospective record review of registry from Kenya ( 96 ), and a retrospective record review of pathology reports in Zambia ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“… 37 For out-of-stock drugs and consumables approved by national health insurance scheme and certain services not approved by the national health insurance scheme, patients are required to pay out-of-pocket regardless of their condition. 38 The vision behind Ghana’s national health insurance scheme is to cover all expenses with the goal of achieving UHC. 9 Our study showed that the national health insurance scheme contributed to decreasing out-of-pocket payments.…”
Section: Discussionmentioning
confidence: 99%